Pengaruh Kualitas Kehidupan Kerja, Pemberdayaan dan Pelayanan Publik Terhadap Kinerja Pegawai Kantor Kecamatan Songgom Dengan Kepuasan Kerja Sebagai Variabel Intervening - Permana, Rindi Ayu; Riono, Slamet Bambang; Aisyah, Nur (CV. Rayyan Dwi Bharata, 2024)
The main objective of this study is to determine how the quality of work life, empowerment, and public service affect the performance of employees at the Songgom District Office, with job satisfaction as an intervening variable. This research uses a quantitative approach with the SmartPLS 3.2.9 analysis tool. The population used in this study consists of all employees working at the Songgom District Office, totaling 138 respondents. The sample in this study was selected using the Stratified Random Sampling method and calculated using the Slovin formula, resulting in a sample size of 103 respondents. Data collection was conducted by distributing questionnaires. The results of the path coefficients for direct and indirect effects show that the quality of work life variable has a significant positive effect on job satisfaction, with a t-value t-table (11.660 1.96) and a sig value of 0.000. Empowerment does not affect job satisfaction, with a t-value t-table (0.506 1.96) and a sig value of 0.613. Public service has a significant positive effect on job satisfaction, with a t-value t-table (5.536 1.96) and a sig value of 0.000. Job satisfaction does not affect employee performance, with a t-value t-table (0.313 1.96) and a sig value of 0.755. The quality of work life has a significant positive effect on employee performance, with a t-value t-table (3.655 1.96) and a sig value of 0.000. Empowerment has a significant positive effect on employee performance, with a t-value t-table (5.570 1.96) and a sig value of 0.000. Public service does not affect employee performance, with a t-value t-table (0.060 1.96) and a sig value of 0.952. The job satisfaction variable is not able to mediate the quality of work life, with a t-value t-table (0.059 1.96) and a sig value of 0.953. Job satisfaction is not able to mediate empowerment, with a t-value t-table (0.027 1.96) and a sig value of 0.979. Job satisfaction is not able to mediate public service, with a t-value t-table (0.039 1.96) and a sig value of 0.957.